Loneliness is associated with different structural brain changes in schizophrenia spectrum disorders and major depression - Fritze, Stefan; Brandt, Geva A.; Volkmer, Sebastian; Daub, Jonas; Akkoc Altinok, Dilsa Cemre; Kubera, Katharina Maria; Berhe, Oksana; Lin, Yuchen; Tost, Heike; Meyer-Lindenberg, Andreas; Hirjak, Dusan (Schizophrenia research, 2025)
Background - Loneliness, distress from having fewer social contacts than desired, has been recognized as a significant public health crisis. Although a substantial body of research has established connections between loneliness and various forms of psychopathology, our understanding of the neural underpinnings of loneliness in schizophrenia spectrum disorders (SSD) and major depressive disorder (MDD) remains limited. - Methods - In this study, structural magnetic resonance imaging (sMRI) data were collected from 57 SSD and 45 MDD patients as well as 41 healthy controls (HC). Loneliness was measured with the German version of the University of California, Los Angeles Loneliness Scale (UCLA-LS). We used FreeSurfer v7.2 for automated parcellation of cortical regions. - Results - SSD patients showed reduced cortical volume and thickness in fronto-parietal and temporal regions when compared to HC (p < 0.05, Benjamini-Hochberg (BH) corr.). In SSD, volume of the right superior temporal gyrus was associated with UCLA-LS total score (p = 0.030; BH corr.). MDD patients showed reduced cortical volume and thickness in fronto-parietal regions (p < 0.05, BH corr.). In MDD, cortical thickness of the right superior parietal cortex was associated with UCLA-LS total score (p = 0.038; BH corr.). - Conclusion - Our study suggests a different neural signature of loneliness in patients with SSD and MDD, comprising temporal and parietal regions responsible for social and attentive processing. Identifying neurobiological mechanisms underlying loneliness is critical for understanding its role in severe mental illnesses and identifying potential therapeutic targets.